MARKERS OF THE ENTERIC INFLAMMATION IN THE EVENT OF INTESTINAL DISEASES: LITERATURE REVIEW - O.F. Tat'yanina; A.S. Potapov; L.S. Namazova; E.G. Tsimbalova; A.G. Kucherenko; A.N. Surkov (Union of pediatricians of Russia, 2008)
The authors provided modern information on the basic noninvasive methods to assess the inflammatory process in the intestine in crohn's disease and colitis gravis. The researchers thoroughly described the opportunities and limitations for the use of faecal calprotectin as a marker of the inflammatory enteric diseases. Importance of this marker for the differential diagnostics of  the inflammatory and functional enteric diseases has been shown.Key words: markers of the enteric inflammation, faecal calprotectin, inflammatory bowel diseases, colitis gravis, сrohn's disease.